Three days, two nights - Suzanne, Jamie; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 2000)
Jessica Wakefield and some of her friends win a trip to Sacramento to compete in an academic tournament.
RL 4.
008-012.
Keywords: Young adult fiction